ANALISIS SWOT TERHADAP UPAYA PASANGAN SUAMI ISTRI ALUMNI SANTRI PONDOK PESANTREN DALAM MEWUJUDKAN KELUARGA SAKINAH - Eri Wijaya; Muh. Kurniawan Budi Wibowo; B Baehaqi (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The background and factors in a family determine his views on the concept of a sakinah family and efforts to make it happen. It can be analyzed using a SWOT analysis whether the family has met the criteria as a sakinah or pre-sakinah family. This study aims to provide insight for every couple who wants to get married, especially for alumni of Islamic boarding schools in an effort to form a sakinah family. The subject of this research is the family of Wahid Firmansyah, one of the alumni of Ma'had 'Aly Makkah Boyolali. This type of research is a qualitative research with data collection techniques in the form of observation, interviews and documentation. While the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the efforts made by married couples alumni of Islamic boarding school students in fostering a household can be used as a concept in realizing a sakinah family. These efforts are choosing the right partner, building a household with the concept of faith and piety, preparing mature provisions from all aspects, utilizing all the potential they have to fulfill their rights and obligations, and resolving every household problem calmly and patiently..